The United Nations since the institutional constitutionalism - Aristizábal Dorado, Andrés Felipe (2023)
Globalization brings many benefits but also imposes big challenges. Multilateralism is found to be an effective mechanism in an increasingly interdependent and globalized world. Hence the United Nations not only provides the appropriate forum for interaction between States, but also from the perspective of institutional constitutionalism, has contributed for strengthening universal juridical conscience by creating a system of values, principles and fundamental rules. Therefore, this article purports to reassert the importance of this international organization and its Charter, which is considered as a global constitution from the global constitutionalism discourse.